Investigation the effects of Na2MoO4 as an inhibitor on electrochemical corrosion behavior of 316L stainless steel in LiBr solution - Amin Rabiei Baboukani; Ali Ashrafi; Ahmad Saatchi (Zaštita Materijala)
The effect of sodium molybdate (Na2MoO4) as an inhibitor at various concentrations of 50, 100 and 200ppm on the electrochemical corrosion behavior of 316L stainless steel in LiBr solution at 60°C was studied by polarization curves, electrochemical impedance spectroscopy (EIS) methods and electron microscopy. Polarization curves indicate that Na2MoO4 acts as mixed-type inhibitor. The corrosion resistance of 316L stainless steel samples increases with the inhibitor concentration up to 200ppm. By increasing the inhibitor concentration from 50ppm to 200ppm, corrosion current density decreases. These results were confirmed by further analysis using a scanning electron microscope.